Magnitude of Viral Load Suppression and Associated Factors among HIV-positive Patients Receiving Antiretroviral Therapy - Acharya , Priti; Neupane, Anil Prasad; Sigdel, Brihaspati; Ghimire, Laxmi; Pant, Madhab Raj; Budhathoki, Abiruchi; Poudyal, Anil (Journal of Nepal Health Research Council, 2023)
Background: Viral load assessment is the preferred method for diagnosing and confirming virologic failure for patients on antiretroviral therapy. This study aimed to assess the proportion of viral load suppression and identify associated factors among HIV-positive patients receiving antiretroviral therapy at the Pokhara academy of health science in Nepal. Methods: This institution-based retrospective cohort study was conducted at Pokhara academy of health science in Pokhara, Nepal. The study included 567 HIV patients who were enrolled between January 2016 and December 2019 and had their viral load measured within a one-year period. Statistical analysis was performed using STATA version 13.0. The proportions of viral load suppression and non-suppression were determined. Bivariate and multivariate logistic regressions were performed to identify factors associated with viral load suppression. Statistical significance was determined at a 95% confidence interval and p < 0.05 Results: Out of the 567 HIV patients, 95.76 % (95% CI: 94.10-97.42) achieved viral suppression. In multivariate analysis, longer duration of antiretroviral therapy treatment (> 3 years) was independently associated with higher odds of achieving viral suppression compared to those on antiretroviral therapy for less than 6 months (adjusted odds ratio [aOR] = 11.98, 95% confidence interval: 1.32-108.81, p < 0.0027). Conversely, individuals in second-line treatment had significantly lower odds of viral suppression compared to those in first-line treatment (aOR = 0.19, 95% CI: 0.05-0.66, p < 0.009). Conclusions: Our study demonstrated a high rate of viral suppression among HIV patients receiving antiretroviral therapy, exceeding the UNAIDS 90-90-90 target. Longer duration of antiretroviral therapy and being in second-line treatment were identified as factors influencing viral load suppression. These findings emphasize the importance of early initiation and adherence to first-line treatment for optimal outcomes. Keywords: ART; HIV/AIDS; viral load suppression